Autonomous digital seismic stations SV - Gryn, D. M.; Verbytsky, S. T. (Geofizicheskiy Zhurnal, 2019)
Seismic exploration is one of the most informative geophysical methods. It gives thorough information on deep and spatial structure of the Earth using features of seismic waves propagation in geological layers with different physical properties. Wave field excited with seismic source propagates in space and time, therefore for its registration we need availability of many observation sites simultaneously resulting in considerable rise in prices cost of seismic information. In turn, absence of numerical seismic data renders impossible development of basic seismicity, seismic monitoring and long-term observation of seismically dangerous processes in big areas of man-made objects. The paper presents autonomous seismic stations developed at the Institute of Geophysics NAS of Ukraine. Universality of seismic stations allows their use for a wide range of seismic and seismological problems. Small weight and size make their transportation easier as well as their mounting in unequipped observation sites in boggy hard-to-reach areas. Long-continued registration of seismic information and big capacity of operative internal memory makes possible their use for passive long-term observations. Several variants of wireless connection have been realized in seismic stations for control of technical condition of the station, inspection of seismic record quality in real time and remote programming for alternation its working regime. Likewise historical review has been presented on development of autonomous seismic stations the most popular in Europe and North America used in large-scale international projects on studies of deep structure of the Earth during the latest 50 years. In addition up-to date passive and active seismic stations used in economic seismicity have been described.